Medisi dan Hakam dalam Hukum Acara Peradilan Agama - Dedi Sumanto; Syamsinah Syamsinah (LP2M Institut Agama Islam Negeri Sultan Amai Gorontalo, 2015)
This paper discusses mediation and hakam (peacemaker) in procedural law the Religious Courts. This article uses the legal approach and it is analyzed by qualitative descriptive method. The results showed that mediation is a step that is carried out through the Islamic Court judges mediators to facilitate dialogue, assist the parties to clarify the needs and desires of justice seekers, set up guide, assist the parties in rectifying differences of views and work towards an acceptable the parties in the settlement binding